A brief review on the spin valve magnetic tunnel junction composed of 2D materials. (20th October 2022) - Elahi, Ehsan; Dastgeer, Ghulam; Sharma, Pradeep Raj; Nisar, Sobia; Suleman, Muhammad; Iqbal, Muhammad Waqas; Imran, Muhammad; Aslam, Muhammad; Imran, Ali
Abstract: Two-dimensional (2D) materials including graphene, hexagonal boron nitride, and transition metal dichalcogenides have revolutionized electronic, optoelectronic and spintronic devices. Recent progress has been made in the knowledge of spin injection, detection, and manipulation utilizing spintronic devices based on 2D materials. However, some bottlenecks still need to be addressed to employ spintronic devices for logical applications. Here, we review the major advances and progress in vertical magnetic tunnel junctions (MTJs) made of various 2D materials as spacer layers between distinct ferromagnetic electrodes. Spin transportation characteristics depending on the magnetic field are investigated by considering the magnetoresistance (MR) and tunneling MR ratio in vertically stacked structures. This review examines the important features of spin transfer through the various spacer 2D materials in MTJs by carefully analyzing the temperature-dependent phenomena. The underlying physics, reliance of spin signals on temperature, quality of junction, and various other parameters are discussed in detail. Furthermore, newly discovered 2D ferromagnets introduce an entirely new type of van der Waals junction enabling effective dynamic control and spin transport across such heterojunctions. Finally, the challenges and prospects of 2D materials-based spin-valve MTJs for improving spintronic devices are discussed in detail.